الخطاب التربوي في برامج أحزاب الحركة الوطنية في الجزائر - اوذاينية, عمر; عزابي, سمية (University of Eloued جامعة الوادي, 2015)
يعد الخطاب التربوي من بين أهم الخطابات التي تساهم في تطور المجتمع و تغييره , فهو يتمثل في جملة التصورات و الرؤى التي تعبر عن صاحب أو جهة الخطاب , ويتضح ذلك من خلال التعرف على أفكاره و مبادئه و كذا الأهداف التي يسعى إلى تجسيدها على ارض الواقع , حيث يأخذ الخطاب التربوي الأهمية في المجتمع لارتباطه بالتربية , وكذا الجهة التي يصدر عنها ومن بين الجهات التي خصصت خطاب تربوي ضمن خطاباتها الأحزاب السياسية و عليه سنحاول في هذا المقال التعرف على الخطاب التربوي عند أحزاب الحركة الوطنية. Speech educational in the National Movement party programs Abstract: The educational discourse is considered as one of the most important discourses which contribute to the development and evolution of the society. It is represented in a sort of ideologies and visions that reflect the owner or the source of the speech, and this will be illustrated through the identification of author's thoughts and principles as well as the goals which he seeks to embody on the ground, Where the educational discourse takes its importance in the society for its association with education as well as the side which it comes from. Among the parties who have dedicated an educational discourse in their speech, we have the political parties. Thus in this article we are going to identify the educational discourse at the level of National Movement parties.
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: الخطاب التربوي - برامج الأحزاب - الحركة الوطنية